ANALYZING THE WILLINGNESS TO WORK AND WILLINGNESS TO PAY FOR RWH IN JAPAN - Xiaohuan Jiang (http://arl.faperta.ipb.ac.id/, 2018)
Citizen participation of rainwater harvesting is a valuable practice to mitigate problems such as groundwater mining, land subsidence, and urban flooding cause by global warming and urbanization in japan. In this study, we defined rainwater harvesting as activities carried out by citizens aimed at using rainwater, and examining the hypothesis that people’s willingness to work (WTW) and willingness to pay (WTP) for rainwater harvesting differ depending on their lifestyles and experience of using rainwater. We conducted a survey over the internet in August 2017, covering 1,794 people in Japan. The survey questions addressed three areas: (1) respondents’ lifestyles, (2) their experience of using rainwater, and (3) their willingness to participate in rainwater harvesting. As the results, we concluded that activities that ask for time or labor are preferable to those that ask for money, and people’s WTW and WTP do in fact differ based on lifestyle. Older people, full-time housewives/husbands, and non-workers have comparatively more time for participating in rainwater harvesting, and showed more interest in activities that ask for time or labor. Men and owners of single-family homes have higher annual incomes and thus greater WTP for rainwater harvesting. Moreover, WTW and WTP differed depending on whether a person had experience using rainwater. Men and younger people having more experience than women and elderly people. However, there were only 10% of the public has experience using rainwater, which shows that there is room to further promote rainwater harvesting.